THE DISPUTE SETTLEMENT OF GOVERNMENTAL CONSTRUCTION WITH FOREIGN BUSINESS ENTITIES IN A CONTRACT OF CONSTRUCTION INFRASTUCTURE SUPPLY - Peni Jati Setyowati; Y Sogar Simamora (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Infrastructure is important and substantial in economic development in Indonesia. The limitations of state revenue to build new infrastructure oblige the government to utilize and fabricate the combination of funding sources in giving public service corporate to foreign entities. This paper dis-cusses the dispute over the Completion of the Construction Contract between the Government and Foreign Parties. The research method used is normative legal research and through a conceptual approach, legislation. The complex implementation of the construction infrastructure supply contract has to be minimized to avoid claiming construction which leads to construction dispute. The issue of Regulation of Indonesia Number 2 Year 2017 on Construction Service has arranged the regulation of construction dispute settlement. According to Article 47, one of the dispute settlements of construction is Dispute Board. There is a legal vacuum in the implementation of its construction service regulation proven by the absence of advanced regulation on the form and procedure of Dispute Board. Keywords: dispute settlement, construction contract, dispute board